The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018 7th International Conference on Renewable Energy Research and Applications (ICRERA) 2018
DOI: 10.1109/icrera.2018.8566828
|View full text |Cite
|
Sign up to set email alerts
|

Influence of The Temporal Resolution of The Water Consumption Profile on Photovoltaic Water Pumping Systems Modelling and Sizing

Abstract: Photovoltaic water pumping could significantly improve water access, particularly in off-grid rural villages of Sub-Saharan Africa. Earlier, we have developed and validated a numerical model of a photovoltaic water pumping system (PVWPS). Such model allows to include the water consumption profile as an input. The current study assesses the influence of the temporal resolution of the water consumption profile on the model accuracy and on PVWPS optimal sizing. This helps to select the adapted temporal resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In addition, the initial investment per unit of water provided may be lower for pumping systems for irrigation than for domestic water. Indeed, domestic water systems often require drilling for accessing drinkable underground water and building water towers, which are two costly operations (Harvey and Reed 2004;Meunier et al 2018). Finally, while the mWTP is higher for domestic uses, agriculture may use higher volumes of water.…”
Section: Discussion Conclusion and Policy Implicationsmentioning
confidence: 99%
“…In addition, the initial investment per unit of water provided may be lower for pumping systems for irrigation than for domestic water. Indeed, domestic water systems often require drilling for accessing drinkable underground water and building water towers, which are two costly operations (Harvey and Reed 2004;Meunier et al 2018). Finally, while the mWTP is higher for domestic uses, agriculture may use higher volumes of water.…”
Section: Discussion Conclusion and Policy Implicationsmentioning
confidence: 99%
“…For convenience, all the measured data were rescaled to an equally spaced temporal resolution of 1 min by nearest interpolation. In addition, references [15] and [26] showed that a temporal resolution of 1 min is sufficient for the modelling and optimal sizing of PVWPS for domestic water access.…”
Section: Methodsmentioning
confidence: 99%
“…In this article, only the source and the temporal resolution of change (see section III) while we use measured data with a 1 minute temporal resolution for the two other inputs of the model ( and ). Indeed, we showed that has a small effect on the model output [12] and we investigated the influence of in a previous article [13].…”
Section: Photovoltaic Water Pumping System Modelmentioning
confidence: 99%